Change of the structure and the digestibility of myofibrillar proteins in Nanjing dry‐cured duck during processing. (5th February 2018) - Du, Xiaojing; Sun, Yangying; Pan, Daodong; Wang, Ying; Ou, Changrong; Cao, Jinxuan
Abstract: BACKGROUND: To investigate the change of bioavailability and structure of myofibrillar proteins during Nanjing dry‐cured duck processing, carbonyl content, sulfhydryl (SH) group, disulfide (SS) group, sodium dodecyl sulfate polyacrylamide gel electrophoresis, surface hydrophobicity, secondary structures and in vitro digestibility were determined. RESULTS: During processing, carbonyl content and surface hydrophobicity increased; SH turned into SS group; α‐helix turned into β‐sheet and random coil fractions. Protein degradation occurred during dry‐curing and drying–ripening stages. The in vitro digestibility of pepsin and pancreatic proteases increased during the salt curing stage and decreased during the drying–ripening stage. CONCLUSION: The increase of digestibility could be attributed to the mild oxidation, degradation and unfolding of proteins while the decrease of digestibility was related to the intensive oxidation and aggregation of proteins. Protein degradation was not a main factor of digestibility during the drying–ripening stage. Results demonstrated that the bioavailability loss of myofibrillar proteins in Nanjing dry‐cured duck occurred during the stage of drying–ripening instead of curing. © 2017 Society of Chemical Industry